The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3233/jad-141239
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Imaging Reveals Visual Pathway Damage in Patients with Mild Cognitive Impairment and Alzheimer's Disease

Abstract: Visual deficits are commonly seen in patients with Alzheimer’s disease (AD), but postmortem histology has not found substantial damage in visual cortex regions, leading to the hypothesis that the visual pathway, from eye to the brain, may be damaged in AD. Diffusion tensor imaging (DTI) has been used to characterize white matter abnormalities. However, there is a lack of data examining the optic nerves and tracts in patients with AD. In this study, we used DTI to analyze the visual pathway in healthy controls,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…In patients with AD, diffuse tensor imaging shows increase in total diffusivity, radial diffusivity and decreased fractional isotropy in the optic nerves (Nishioka et al 2015). This technique is sensitive and specific and has been used to demonstrate beta-amyloid plaques ex vivo in mouse and human retina and in vitro screening of chemical compounds for amyloidogenesis.…”
Section: Fluorescent Ligand Eye Scanning System (Fles)mentioning
confidence: 99%
“…In patients with AD, diffuse tensor imaging shows increase in total diffusivity, radial diffusivity and decreased fractional isotropy in the optic nerves (Nishioka et al 2015). This technique is sensitive and specific and has been used to demonstrate beta-amyloid plaques ex vivo in mouse and human retina and in vitro screening of chemical compounds for amyloidogenesis.…”
Section: Fluorescent Ligand Eye Scanning System (Fles)mentioning
confidence: 99%
“…On the other side, Alichniewicz et al (17) found decreased activation in frontal eyes fields, and Jacobs et al (18) found increased activation in the visual pathways of MCI and early AD patients. By using diffusion tension imaging, Nishioka et al (19) demonstrated that the visual pathway from the eyes to the brain is affected both in the MCI and, to a greater extend, in the AD; pathological changes were found mainly in the optic nerves. In a heterogenous series of patients with tau pathology, Rahimi et al (20) found tau deposition both in the optic nerve and in the lateral geniculate nucleus.…”
Section: Resultsmentioning
confidence: 99%
“…doi:10.1017/S1041610219001418 extracellular space enlargement in GM (Elman et al, 2017;Neil et al, 2002). Many previous DTI studies have revealed altered FA and MD even in normal aging (Abe et al, 2008;Benedetti et al, 2006;Garcia-Lazaro et al, 2016), age-related neurodegenerative diseases, such as mild cognitive impairment and Alzheimer's disease (Nesteruk et al, 2016;Nishioka et al, 2015), demyelinating diseases, such as multiple sclerosis (de Kouchkovsky et al, 2016), and neuropsychiatric diseases, such as depression and schizophrenia (Jiang et al, 2017;Singh et al, 2016). Most of these studies have focused on WM or deep GM such as the hippocampus, because these brain regions have high directionality in water diffusion (Manna et al, 2015;Ziyan and Westin, 2008), whereas water diffusion in the cerebral cortex has an isotropic direction at the level of conventional DTI resolution (Elman et al, 2017).…”
Section: Introductionmentioning
confidence: 99%